From Abject to Subject: Reinterpretation of Women’s Identity in Laetitia Colombani’s Novel La Tresse - Sulfi Baridah Hanum; Wening Udasmoro (MOZAIK HUMANIORA, 2026)
This study aims to explore the practices of abjection experienced by women from diverse backgrounds and their responses in the novel La Tresse. The research method used is a qualitative descriptive method combined with content analysis to describe the abjection experienced by the female characters in the novel. Data in the form of textual excerpts were collected through close reading, tabulated, classified into several categories, and translated into Indonesian. The data were then analyzed through the lens of Julia Kristeva’s (1982) concept of abjection. The findings reveal that abjection is experienced by women regardless of their backgrounds, indicating that it extends beyond the individual level to constitute a structural issue across social contexts. Furthermore, the analysis demonstrates that each woman mobilizes distinct forms of resistance, emphasizing that women’s identities are not passively determined by oppressive structures, but are actively forged through resistance and negotiation. This study offers new insights into how contemporary literature portrays the agency of abject women across different cultures.